Deciding to Persist: Adversity, Values, and Entrepreneurs’ Decision Policies - Holland, Daniel V.; Shepherd, Dean A. (Entrepreneurship Theory and Practice, 2013)
Entrepreneurial persistence occurs when the entrepreneur chooses to continue with an entrepreneurial opportunity regardless of counterinfluences or enticing alternatives. The decision to persist is influenced by personal characteristics and by feedback from the environment relative to thresholds. Using a conjoint experiment, we investigate how adversity and values influence the weight placed on the decision attributes for the persistence decisions of 100 entrepreneurs. The findings suggest that the persistence decision policies are heterogeneous depending on the level of adversity experienced and the individual values held by the entrepreneurs. The results provide interesting insights into why and how entrepreneurs choose to persist.